Pengaruh Konsentrasi terhadap Penyerapan Ion Zn(II) Menggunakan Biosorben Kulit Langsat (Lansium domesticum Corr) - Lestari, Kardina; Kurniawati, Desy (MASALIQ, 2024)
Excessive discharge of heavy metals in the environment can have negative effects on the environment and human health. environment and human health, one of which is the metal ion Zn2+. To overcome the increase in heavy metals biosorption method is used. The purpose of this study is to determine the general conditions of the initial concentration of Zn2+ that can be absorbed by langsat skin as well as the isotherm used. The results showed that optimum absorption of Zn2+ metal ions occurred at an initial concentration of 400 ppm solution and decreased with increasing concentration. The optimum absorption of Zn2+ metal ions occurs at an initial concentration of 400 ppm solution and increases with increasing concentration and decreases when it reaches the optimum state. The maximum absorption capacity obtained was 11.7168 mg/g. The capacity of biosorption of Zn2+ ions fulfills the Langmuir Isotherm equation with R2 of 0.9994.